Profile of Hypertensive Patients Indicated to Surgical Procedures in The Oral Cavity - Borja de Melo, Téssia Richelly Nóbrega; Barros Freitas, Dalva Zélia; Machado Patriota, Irley Gonzaga; Rivera, Giovani Amado; Araújo, Flaviano Falcão de (The Journal of Dentists, 2023)
Objective: The present study aimed to evaluate the profile of hypertensive patients, indicated surgical procedures in the oral cavity. Methods: Treated an observational and cross-sectional research, with a quantitative approach, whose sample consisted of 50 medical records of patients diagnosed with arterial hypertension. A survey was conducted at the Clinical School of the University Center of Patos - UNIFIP / PB. Data collection was performed by a single examiner. The information was distributed on the form prepared for this purpose. The data were computed using the SPSS software for Windows, v. 22, and analyzed by descriptive statistics that use as frequencies, media and standard deviations. Results: The average age of the patients was 48 years. The majority of the sample was composed of women (58%); by white patients (40%); non-smoking patients (52%) and ex-alcoholics (36%). As for diseases associated with hypertension, diabetes was more prevalent (18%), being also the most frequent among the variations associated with family history (20%). The drug most used by patients was Losartana (34%); and the local dental anesthetic, a 2% Mepivacaine associated with Epinephrine 1,100.00 (56%). Most patients were seen in the morning shift (58%). Conclusions: It was concluded that white non-smoking women and ex-alcoholics were more prevalent among hypertensive patients, with diabetes being a disease more associated with arterial hypertension.